Financial Inclusion and Rural Development: Empowering Micro-entrepreneurs in Lubuk Beringin, Bungo Regency, Jambi, Indonesia - Abu Bakar; Widya Pratiwi; Eva Marlina; Sasmita Rusnaini; Mardiansyah; Silvia Jesika; Zulkifli; Darmawanto; Syah Amin Albadry; Hamirul (Indonesian Community Empowerment Journal, 2024)
Micro-entrepreneurs in rural Indonesia often face challenges in accessing financial services and developing sustainable business practices. This community service initiative aimed to empower micro-entrepreneurs in Lubuk Beringin, Bungo Regency, Jambi, Indonesia, by promoting financial inclusion and rural development. A mixed-methods approach was employed, incorporating surveys, focus group discussions, and in-depth interviews to assess the needs and challenges of micro-entrepreneurs. Based on the findings, a comprehensive program was designed and implemented, encompassing financial literacy training, business development workshops, and access to microcredit facilities. The program resulted in increased financial literacy, improved business skills, and enhanced access to financial resources among the participants. Data indicates a 20% increase in average monthly income and a 15% rise in business savings among participating micro-entrepreneurs six months after program completion. Additionally, the program fostered a sense of community and collaboration among the participants. This initiative demonstrates the vital role of public administration in empowering micro-entrepreneurs through financial inclusion and rural development strategies. By providing access to financial knowledge, skills, and resources, public administration can contribute to sustainable economic growth and improved livelihoods in rural communities.